820. Optimal Specimen Source(s) for Carbapenemase-Producing Acinetobacter Colonization Screening. (4th December 2021) - Dale, Jennifer; Anacker, Melissa; Craft, Bradley; Gross, Annastasia; Fischer, Jill; Blanding, Justin; Lindemann, Stephanie; Tang, Angela; Brister, Sarah; Dowdell, Ashlie; Stein, Emma; O'Malley, Sean; et al.
Abstract: Background: Infection prevention (IP) strategies are implemented to limit the transmission of healthcare-associated infections (HAIs), which are estimated to occur in 1 out of 31 hospitalized patients per day in the United States. Carbapenem-resistant Acinetobacter (CRA) cause HAIs classified as an urgent threat by CDC. When carbapenemase-producing CRA (CP-CRA) are identified, containment strategies are implemented, including screening patients at high risk for colonization with CP-CRA. Point prevalence surveys (PPS) are conducted to assist with HAI outbreak investigations and identify colonized patients. Methods: Herein, we describe results from culture-based CP-CRA colonization testing of multiple specimen sources (rectal, skin [axilla/groin or groin], respiratory, and/or wound). A total of 744 PPS specimens from 356 patients, across six states, were obtained from February 2019 to May 2021 for CP-CRA colonization screening including 30% (224/744) rectal, 52% (390/744) skin, 10% (73/744) respiratory, and 8% (57/744) wound sources. The specimens were plated onto both non-selective (blood agar) and selective media (MacConkey, ESBL CHROMagar, Acinetobacter CHROMagar), and RT-PCR was performed for detection of the Acinetobacter -specific carbapenemase genes bla OXA-23, bla OXA-24, and bla OXA-58. Results: Twelve percent (90/744) of specimens, representing 17% (62/356) of patients, were positive for detection of bla OXA-23 and/or bla OXA-24 CP-CRA. The majority (96%) of CP-CRA harbored bla OXA-24 . Of the 62 colonized patients, 52% (32/62) had more than one collection source and 47% (15/32) of those had more than one source positive for CP-CRA. There was no consensus regarding a single source type across positive specimens. However, rectal or skin swab collection alone would potentially miss 2% (4/163) or 8% (14/186) of positive specimens, respectively. Conclusion: These data suggest that rectal or skin source collection alone could be sufficient for detection of CP-CRA. Overall, multiple factors should be considered to guide the source(s) for CP-CRA specimen collection, such as infection type, regional prevalence, patient factors, and/or IP gap(s) within a facility. Disclosures: All Authors : No reported disclosures